Uji Emisi Gas CO Dari Pembakaran Briket Tandan Kosong Sawit (TkS) Pada Skala Rumah Tangga - Wanda Putri Saragi; Hafidawati Hafidawati; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Biomass is an alternative energy source because it has hydrocarbon molecules. In this study, processing of biomass into briquettes from plantation waste is carried out in the form of Oil Palm Empty Bunches (TKS). In its use, briquettes through the combustion process will produce carbon monoxide gas emissions which have many negative impacts. Therefore, this study was conducted to determine the results of CO concentration resulting from the combustion of EFB briquettes on variations in emission measurement distances. Emission testing was carried out using the Environmental Combustion Analyzer Model 450. The results of the analysis obtained the concentration of CO parameters for EFB briquettes with variations in the measurement distances of 0 cm, 10 cm, 20 cm and 30 cm, namely 162 mg/Nm3, 141 mg/Nm3, and 74 mg. /Nm3 and 69 mg/Nm3. The test results for a safe distance that can be used for cooking is at a distance of 30 cm from the emission source, namely the emission test results are below the quality standard of 69 mg/Nm3 Keywords: biomass, briquette, emissions measurement distance, empty bunch of palm, carbon monoxide